(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Just before the WWII the communist organization in Serbia managed to attract support from a large number of women. However, the response and participation of women in the national liberation troops was significant, unexpected and surprising for the leaders of the communist movement. Unlike other parts of Yugoslavia, educated young women, who had already been involved in the communist association, joined the partisan units in Serbia. The lives of those women were threatened because of their orientation. They were motivated by the struggle for freedom, and even though awareness of the promised emancipation was present, it was not a decisive factor. A significant number of women joined the uprising in 1941, but soon after it had been crushed, the majority ended up rejected and undefended. The number of women who were willing to join the troops decreased markedly in 1942. The leaders of the partisans then began to encourage women to take part in the war, breaking the resistance towards their participation in the military. Nevertheless, the number of women among partisans continued to lessen and in 1945 a massive demobilization of women took place. Even though it was short-lived, the participation of women in the partisan units left a significant mark. The acceptance of women into the army served not only as a resource of additional manpower, but also as a confirmation of the communist movement’s prewar support for gender equality.